Safety evaluation of the food enzyme lysophospholipase from the genetically modified Trichoderma reesei strain DP‐Nyc81 - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme lysophospholipase (2‐lysophosphatidylcholine acylhydrolase, EC 3.1.1.5) is produced with the genetically modified Trichoderma reesei strain DP‐Nyc81 by Genencor International B.V. The genetic modifications do not give rise to safety concerns. The food enzyme is free from viable cells of the production organism and its DNA. It is intended to be used in the processing of cereals and other grains for the production of glucose syrups and other starch hydrolysates. Since residual amounts of food enzyme–total organic solids are removed during these food manufacturing processes, dietary exposure was not calculated and toxicological studies were considered unnecessary. A search for the identity of the amino acid sequence of the food enzyme to known allergens was made and no match was found. The Panel considered that the risk of allergic reactions upon dietary exposure cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.